The making of urban América; a history of city planning in the United States - Reps, John W. (New Jersey : Princeton Universit, 1965)
Siglos XVII a XX
Keywords: PLANIFICACION URBANA; ESTADOS UNIDOS; URBANISMO; HISTORIA; CIUDADES; AMERICA